FORUM EXAMINES COUNTRY’S ECONOMIC ACHIEVEMENTS IN FACING 2020 - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, October 2015 – It is hoped that Malaysia will attain a highincome economy status by the year 2020 in line with the agenda of Vision 2020 as outlined by the government.